Energy Use vs Staff Performance at Soekarno Hatta: Partial Least Squares Structural Equation Modeling and Importance Performance Map Analysis Approach - Mc Ali Muchtar; Erry Rimawan; Mawardi Amin (Jurusan Matematika FMIPA Universitas Pattimura, 2025)
This study investigates the operational impact of four key infrastructure systems (HVAC, lighting, electrical equipment, and internal transport) on staff performance at Terminal 3 of Soekarno-Hatta International Airport. Despite consuming 86.59% of the terminal’s energy, HVAC systems show no statistically significant contribution to staff performance. In contrast, lighting, electrical equipment, and internal transport significantly improve staff productivity, with internal transport having the highest influence. A structural equation modeling approach using PLS-SEM and Importance-Performance Map Analysis (IPMA) was employed to analyze data from 400 respondents. The model yielded strong explanatory (R² = 0.613) and predictive relevance (Q² = 0.505), validating its robustness. Findings suggest that energy management in airport terminals should shift from consumption-based to performance-based prioritization, favoring infrastructure investments that directly enhance operational efficiency.